Bridging for cross protocol talk in IOT devices using windows communication foundation - Mamlook, Rustom; F. Khan, Omer; Sultan Mohammed, Thabit (International Journal of Engineering and Technology, 2018)
In the Internet of Things (IoT), multiple communication protocols are used to connect the smart device. Wi-Fi, Xbee, ZigBee, Bluetooth, and LoRaWAN are some of the communication channels utilized for connectivity by devices using some IoT platform.In order to enable the development of smart services for IoT platforms, there are solutions by different vendors to connect between IoT devices. For example, multiple IoT platforms are available in the market namely IoTivity platform developed by Open Connectivity Foundation (OCF), AllJoyn platform from All Seen Alliance, Weave made by Google, and Home Kit by Apple. In view of such segmentation of IoT platforms, IoT Applicationâ€™s development has been made complex, where IoT device and accompanying application compatibility with available platforms requires support for multiple protocols.To simplify the complexity introduced by multiple platforms, M2M [4] International standard was already proposed as the bridge for integrating IoT protocols. In our paper, we implement a proxy web service using Windows Communication Foundation (WCF) as a way to translate communication in one IoT protocol to another. In our implementation of middleware, we allowed the MQTT broker to accept messages, which were passed, to the Web Service from various devices over Hyper Text Protocolâ€™s POST or GET Commands. Bridging between WCF Web Service and MQTT broker was enabled with duplex communication. Hence, devices supporting either HTTP protocol or MQTT protocol were able to communicate transparently.Â Â